2010
DOI: 10.1007/s11999-010-1474-6
|View full text |Cite
|
Sign up to set email alerts
|

The Repicci II® Unicondylar Knee Arthroplasty: 9-year Survivorship and Function

Abstract: Background Unicompartmental knee arthroplasty (UKA) is a recognized procedure for treatment of medial compartment osteoarthritis. UKA using minimally invasive surgery (MIS) has the theoretical advantage of less bone resection and quicker rehabilitation. Whether the function of patients with UKA compares with that of patients with conventional TKA is unclear. Questions/purposes We determined (1) the length of stay and complications associated with a short-stay MIS protocol; (2) whether MIS techniques allow for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…In contrast, O’Donnell et al prospectively followed 100 patients who underwent 114 UKAs with the study system under a short-stay MIS protocol. With 22 patients revised a mean of 6.2 years later, the 9-year survival of the prosthesis was estimated at 78% [18]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, O’Donnell et al prospectively followed 100 patients who underwent 114 UKAs with the study system under a short-stay MIS protocol. With 22 patients revised a mean of 6.2 years later, the 9-year survival of the prosthesis was estimated at 78% [18]. …”
Section: Discussionmentioning
confidence: 99%
“…The popularity of the Repicci prosthesis has waned recently due to variable survivorship outcomes, the need for a freehand bone sculpting, and fears over subsidence of the tibial inlay. While good short- and mid-term functional results have been reported [17, 18], and a study by the device inventor reported low revision rates after 8 years [19], one investigation [18] reported lower mid-term survivorship and rates of revision than those recorded for other UKA systems [2022]. However, the longevity of UKA is highly dependent on the surgical technique, as well as on implant position and alignment [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…(Intra-observer variability, FTA = 0.87, TPA = 0.83, PTS = 0.80). Moreover, since limb alignment and survivorship in a UKA are very sensitive to change in JL [39][40][41]; a previously validated method, based on the correlation between femoral width and the distance from the femoral adductor tubercle to JL, was used for radiographic JL measurement [42]. Briefly, the JL was assessed by calculating the distance from the adductor tubercle according to the femoral width multiplied by a validated ratio [43].…”
Section: Issn: 2334-2846mentioning
confidence: 99%
“…Based on current survival rates at ten years follow-up, survival ranges from 53 to 95 % [1][2][3][4][5][6][7][8][9][10][11]. The term "failure" can be defined in a number of ways.…”
Section: Introductionmentioning
confidence: 99%